Caring for patients with Suicidal Behaviour: an Exploratory Study - DOYLE, LOUISE (My University, 2007)
Presentation to the Emergency Department (ED) of patients with suicidal behaviours is relatively common. While many of these patients may be referred on to specialist mental health services, many are either discharged with no psychiatric follow-up or leave before being seen. There is therefore an increasing onus on the staff of Emergency Departments to become involved in the assessment and initial management of this patient group. The aim of this study was to describe the experiences and challenges that nurses encounter when caring for patients who present to the ED with suicidal behaviour. Forty-two ED nurses completed a 15-item semi-structured questionnaire. Participants in this study identified risk assessment as part of their role but did not focus on psychosocial assessment or psychological management of this patient group. Feelings of sympathy and compassion were reported towards these patients; however, there was often a prior judgement of the perceived ‘genuineness’ of the presentation. Finally, challenges experienced included a lack of appropriate communication skills and insufficient resources within the ED department to adequately care for this vulnerable patient group.
PUBLISHED
Keywords: Suicidal behaviour, Emergency Departments, Nurses Experiences, Challenges.; Suicidal behaviour, Emergency Departments, Nurses Experiences, Challenges.